Treatment of Brain Arteriovenous Malformations - Beneš, Vladimír; Bubeníková, Adéla; Skalický, Petr; Bradáč, Ondřej (Advances and technical standards in neurosurgery, 2024)
Brain arteriovenous malformations (AVMs) are a rare entity of vascular anomalies, characteristic of anatomical shunting where arterial blood directly flows into the venous circulation. The main aim of the active treatment policy of brain AVMs is the prevention of haemorrhage. There are well-established treatment strategies that continually improve in their safety and efficacy, primarily due to the advances in imaging modalities, targeted and novel techniques, the development of alternative treatment approaches, and even better experience with the disease itself. There are interesting imaging novelties that may be prospectively applicable in the decision-making and planning of the most effective treatment approach for individual patients with intracranial AVM. Surgery is often considered the first-line treatment; however, each patient should be evaluated individually, and the risks of the active treatment policy should not overcome the benefits of the spontaneous natural history of the disease. All treatment modalities, i.e., surgery, radiosurgery, endovascular embolization, and observation, are justified but need to be meticulously selected for each individual patient in order to deliver the best treatment outcome. This chapter deals with historical and currently applied dogmas, followed by introductions of advances in each available treatment modality of AVM management.
Keywords: Endovascular methods; lidé; Embolization, Therapeutic; neurochirurgické výkony; Endovascular Procedures; intrakraniální arteriovenózní malformace; Arteriovenous malformation; endovaskulární výkony; Natural history; Surgery; radiochirurgie; Intracranial Arteriovenous Malformations; Humans; Radiosurgery; terapeutická embolizace; Neurosurgical Procedures